Genetic heterogeneity in rapid onset dystonia-parkinsonism: description of a new family. Issue 6 (16th May 2005) - Kabakci, K; Isbruch, K; Schilling, K; Hedrich, K; de Carvalho Aguiar, P; Ozelius, L J; Kramer, P L; Schwarz, M H R M; Klein, C
Abstract : Rapid onset dystonia-parkinsonism (RDP) is a rare movement disorder with autosomal dominant inheritance, characterised by sudden onset of dystonic spasms and slowness of movement. To date, three families have been described that share linkage to the same location on chromosome 19q13, designated DYT12 . Very recently, mutations in the ATP1A3 gene at the DYT12 locus have been demonstrated in seven unrelated patients, including the three previously linked families. A large RDP family is reported here, with eight definitely and one possibly affected members, that is not linked to the DYT12 region and has no mutation in the ATP1A3 gene. Predominant cranial-cervical involvement of dystonia occurred in this family, which has also been described in patients with idiopathic torsion dystonia linked to the DYT6 region on chromosome 8 and is a rare finding in DYT1 dystonia. Molecular genetic analysis also excluded linkage to the DYT6 locus and the GAG deletion in DYT1, suggesting at least one additional RDP gene.